Explicit Instructional Interactions: Exploring the Black Box of a Tier 2 Mathematics Intervention. (March 2017) - Doabler, Christian T.; Clarke, Ben; Stoolmiller, Mike; Kosty, Derek B.; Fien, Hank; Smolkowski, Keith; Baker, Scott K.
A critical aspect of intervention research is investigating the active ingredients that underlie intensive interventions and their theories of change. This study explored the rate of instructional interactions within treatment groups to determine whether they offered explanatory power of an empirically validated Tier 2 kindergarten mathematics intervention. Direct observations were conducted in 46 interventions groups, involving approximately 228 students. Multilevel structural equation models revealed that fall mathematics achievement significantly and negatively predicted the rate of academic feedback. Specifically, intervention groups with lower student mathematics achievement at the start of the kindergarten year received higher rates of academic feedback. Analyses also suggested that latent rates of instructional interactions were not significantly correlated with gains on student mathematics outcomes. Implications are discussed in relation to specifying the underlying mechanisms to intensify mathematics interventions, documenting local adaptation of intervention implementation, and examining possible threshold effects of instructional interactions.